DETECTION OF TAST SALT TOLERANCE GENE IN THREE SELECTED WHEAT GENOTYPES FOR SALINITY STRESS UNDER SALINITY CONDITIONS - Majeed, D. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The aim of this study is detection of salt tolerant gene (TaST) selected wheat genotypes for salt tolerance (1H, 2H , 3H) through plant breeding program as compared with local cultivars (sensitive) under salinity condition. Quantitative reverse transcription-PCR (q-RT-PCR) was used to detect TaST salt tolerant gene in these selected genotypes. Also chlorophyll and organic compounds contents were estimated in the upper leaves of the selected genotypes and local cultivars. Results of the PCR showed that the gene band of TaST appeared only in the selected genotypes with length 175bp at both salinity conditions, while this band absent in the local cultivars, (sensitive) (Iraq and latefyi), also at both salinity conditions. All the selected genotypes had the same band size (175bp). Chlorophyll content in the upper leaves of selected genotypes increased at salinity treatment, while it decreased in the leaves of local cultivars at this treatment as compared with non-saline conditions. The results also, showed that the selected genotypes had the highest organic compounds in their leaves, especially under salinity condition. It can be concluding that the selected genotypes (1H, 2H, and 3H) were more salt tolerance than local cultivars (Iraq, latefyi).